Biochemistry in the Lab : a manual for undergraduates - Lasseter, Benjamin F. (CRC Press, 2020)
"Biochemistry in the Lab: A Manual for Undergraduates presents a comprehensive approach to modern biochemistry laboratory teaching together with a complete experimental experience, from molecular biology, cloning, and protein expression, to purification and characterization"--